Association of a specific major histocompatibility complex class IIβ single nucleotide polymorphism with resistance to lactococcosis in rainbow trout, Oncorhynchus mykiss (Walbaum). Issue 1 (8th January 2014) - Colussi, S; Prearo, M; Bertuzzi, S A; Scanzio, T; Peletto, S; Favaro, L; Modesto, P; Maniaci, M G; Ru, G; Desiato, R; Acutis, P L
Abstract Major histocompatibility complex (MHC) loci encode glycoproteins that bind to foreign peptides and initiate immune responses through their interaction with T cells. MHC class II molecules are heterodimers consisting of α and β chains encoded by extremely variable genes; variation in exon 2 is responsible for the majority of observed polymorphisms, mostly concentrated in the codons specifying the peptide‐binding region. Lactococcus garvieae is the causative agent of lactococcosis, a warm‐water bacterial infection pathogenic for cultured freshwater and marine fish. It causes considerable economic losses, limiting the profitability and development of fish industries in general and the intensive production of rainbow trout, Oncorhynchus mykiss (Walbaum), in particular. The disease is currently controlled with vaccines and antibiotics; however, vaccines have short‐term efficacy, and increasing concerns regarding antibiotic residues have called for alternative strategies. To explore the involvement of the MHC class II β‐1 domain as a candidate gene for resistance to lactococcosis, we exposed 400 rainbow trout to naturally contaminated water. One single nucleotide polymorphism (SNP) and one haplotype were associated with resistance (P < 0.01). These results are promising for using MHC class IIβ as a molecular marker in breeding rainbow trout resistant to lactococcosis.